Is it time for an elemental and humoral (re)turn in archaeology? - Jones, Richard; Miller, Holly; Sykes, Naomi (Cambridge University Press, 2016)
This paper asks whether archaeologists might profitably re-engage with the pre-Enlightenment doctrines of elemental philosophy and humoral theory as paradigms more relevant for archaeological interpretation in certain contexts than much of current theoretical discourse. These ancient cosmologies are here reconceptualized to suggest ways in which archaeologists might provide fairer representations of past cultures, through the readoption of ideas that they understood rather than through the imposition of more recent and thus anachronistic frames of analytical reference. In four brief case studies, the paper seeks to show how the foregrounding of elemental and humoral theories might lead to new ways of thinking about the study and interpretation of the landscape, material culture, consumption and the senses. Through them, the paper looks to encourage reflection on whether elemental and humoral theories represent the intellectual paradigms that archaeologists have been striving to invent since the discipline's creation.